Pattern of Skin Diseases among Children Under 5 Years of Age: A Snapshot from a Tertiary Care Hospital of Eastern India - Sumita Sharma; Farheen Begum; Lipilekha Patnaik; Maytree Panda (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Background: Children, especially in underdeveloped countries, are more susceptible to acquire skin infections than adults due to factors such as nutrition, environmental conditions, genetic makeup, immune status, socioeconomic status, hunger, overcrowding, and personal hygiene. Objective: To assess the pattern of dermatoses among children under 5 years of age attending a tertiary care hospital. Methods: This observational study of 283 patients aged up to 5 years attending the department of dermatology, venereology, and leprosy was conducted from July 2022 to June 2023. Data were collected using a predesigned and pretested questionnaire which included sociodemographic profiles, general examination, family history, environmental conditions, genital exposure like syphilis, gonorrhea, chlamydia, and genital herpes of mothers during pregnancy and child birth, genetic factors, cultural factors, nutritional status, and confirmatory diagnosis. All data were entered into Excel sheets and statistically analyzed by IBM SPSS software version 26, and Chi-squared test was used to compare the associations. Results: Children in between 3 and 5 years of age formed the majority (43.81%). Females (66.1%) outnumbered males. Most of the skin diseases among under-5 children were reported in the summer season (March to June); infections constituted the most (46.64%), followed by eczema (19.78%), hypersensitivity disorders (14.48%), nevi (4.59%), papulosquamous disorders (3.53%), pigmentary (3.18%), transient noninfective physiological neonatal conditions (3.53%), disorders of sweat gland (2.47%), hair (0.70%), and miscellaneous dermatoses (1.06%). Among infections, bacterial infections (47.72%) were more common, followed by viral (28.03%), fungal (17.42%), and parasitic (6.81%). Conclusions: Infections/infestations constituted the most among the dermatoses in children up to 5 years of age. As they are preventable, educating the parents, guardians, care takers, and teachers in the preschool can improve the wellbeing of children by limiting the transmission of these diseases.